Dynamics and Origin of Transparent Exopolymer Particles in the Oyashio Region of the Western Subarctic Pacific during the Spring Diatom Bloom - Nosaka, Yuichi; Yamashita, Youhei; Suzuki, Koji (Frontiers in Marine Science, 2017)
The seasonal biological drawdown of the partial pressure of CO2 (pCO2) in the surface waters of the Oyashio region of the western subarctic Pacific is one of the greatest among the world’s oceans. This is attributable to spring diatom blooms. Transparent exopolymer particles (TEPs) are known to affect efficiency of the biological carbon pump, and higher TEP levels are frequently associated with massive diatom blooms.However, TEP dynamics in the Oyashio region remain unclear. This study investigates the TEP distribution from three cruises during the spring diatom bloom periods in 2010 and 2011. TEP concentrations varied from < 15 to 196 ± 71 µg xanthan gum equiv. L-1 above 300 m and generally declined with depth. Vertical TEP concentrations were significantly related not only to chlorophyll a concentrations but also to bacterial abundance. Average TEP concentrations within the mixed layer were significantly higher during the bloom (155 ± 12 µg Xanthan gum equiv. L-1) than in the post-bloom phase (90 ± 32 µg Xanthan gum equiv. L-1). In contrast, bacteria abundance within the mixed layer changed little during the bloom to post-bloom phases. These results suggest that the abundance of phytoplankton greatly contributed to dynamics of the TEP distribution. To evaluate the ability of the phytoplankton to produce TEP, an axenic strain of the diatom Thalassiosira nordenskioeldii, which is a representative species of Oyashio blooms, was examined within a batch culture system. Cell abundance-normalized TEP and dissolved organic carbon (DOC) production rates changed simultaneously with growth of the strain. Although these production rates were significantly higher in the stationary phase than in the exponential growth period, values of the TEP/DOC ratio changed little throughout incubation. These findings suggest that TEP production in the Oyashio region may be enhanced by an increase in DOC production from spring diatoms.